2016
DOI: 10.1002/aoc.3445
|View full text |Cite
|
Sign up to set email alerts
|

New heteroleptic palladium(II) dithiocarbamates: synthesis, characterization, packing and anticancer activity against five different cancer cell lines

Abstract: Two new heteroleptic palladium(II) complexes have been synthesized by reacting equimolar quantities of palladium(II) chloride, sodium 4‐(2‐methoxyphenyl)piperazine‐1‐carbodithioate and diphenyl‐p‐tolylphosphine (1) or tri‐p‐tolylphosphine (2). Complexes 1 and 2 have been characterized using elemental analysis, Fourier transform infrared spectroscopy, multinuclear NMR (1H, 13C and 31P) spectroscopy and single‐crystal X‐ray analysis. The latter technique confirms a pseudo square‐planar geometry in which two adja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Aly et al, Nabipour et al, Manav et al, and Ghorbani-Vaghei et al identified numerous applications of dithiocarbamates in biological studies as anticancer [13], antifungal [13], antibacterial [99, 100], rodent repelling [101], growth depressing [102], and toxicity studies [18]. According to Khan et al, palladium(II) and platinum(II) coordination compounds of dithiocarbamates attracted a lot of attention due to their better anticancer, antitumour, and less toxic properties than cisplatin [103]. They further stated that the presence of nitrogen and sulfur (N and S) coordination modes in ligands used to synthesize platinum(II) complexes helped to lower the challenges linked with cisplatin's toxicity and its analogues.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…Aly et al, Nabipour et al, Manav et al, and Ghorbani-Vaghei et al identified numerous applications of dithiocarbamates in biological studies as anticancer [13], antifungal [13], antibacterial [99, 100], rodent repelling [101], growth depressing [102], and toxicity studies [18]. According to Khan et al, palladium(II) and platinum(II) coordination compounds of dithiocarbamates attracted a lot of attention due to their better anticancer, antitumour, and less toxic properties than cisplatin [103]. They further stated that the presence of nitrogen and sulfur (N and S) coordination modes in ligands used to synthesize platinum(II) complexes helped to lower the challenges linked with cisplatin's toxicity and its analogues.…”
Section: Biological Applicationsmentioning
confidence: 99%
“…The higher activity of compound 17 was possibly due to its higher stability as compared to 16, as determined by density functional theory. 40 Arjmand et al designed and synthesized tin iminodiacetate conjugated with piperazinediium cation 18 as a potential antitumor agent. Conjugate 18 showed significant cytotoxic activity versus HCT15, HOP62, MCF7, and SK-OV-3 cancer cell lines, having GI 50 values of less than 10 µg/mL.…”
Section: Metal Complexes Of Piperazine Derivativesmentioning
confidence: 99%
“…Complexes 3 and 4 were fully characterized by 1 H NMR, 13 C{ 1 H} and 31 P{ 1 H} NMR and IR spectroscopy as well as mass spectrometry and elemental analysis. The 1 H and 31 P{ 1 H} NMR spectra both showed an upfield shift in their resonances due to the electron back-donation from the palladium center to the dithiocarbamate ligand 26 and the σ-donation of the adjacent dithiocarbamate ligand. In addition to the new resonance observed at 30.5 ppm for both 3 and 4 in the 31 P{ 1 H} NMR spectra, the presence of the hexafluorophosphate counteranion was evidenced by a characteristic septet.…”
Section: Synthesis Of Palladium(ii) Complexes Scheme 3 Summarizes Thmentioning
confidence: 99%